Análisis de la falla del techo flotante de un tanque de almacenamiento de gasolina. - Rivera Beltrán, Yichsy; Fernández García, Briseida; Davis Harriett, Juan; Llovet de Armas, Nelson F.; Cueli Corugedo, Alexander; López Guerra, Silio (Revista CENIC Ciencias Quimicas)
In this work, the cause of the failure in the floating roof of a tank that stores gasoline in an oil refinery was determined. By visual inspection, the high deterioration of the aluminum plates that make up the membrane was observed and a solid scattered on them was perceived. The structural study of the alloy was carried out using Electric Arc Emission Spectrometry and Metallography. The corrosion products were characterized by Xray diffractometry. The material matched 3003 aluminum alloy and no structural deficiencies were found that would sensitize the material to corrosion. On the surface exposed to humidity and oxygen, localized attack was evidenced. The cause of the failure was galvanic corrosion, due to differences in oxygen concentration between the covered areas of the solid and the free areas of the same.